Review of Economic Trends and State Plan 1985-86 (As presented to the Legislative Assembly in August, 1985) - Planning Commission (Planning Commission, 1985)
The provisional estimates for 1983-84 indicate that the State Income at constant (1970- 1971) prices grew at a rate of 7.3 per cent over 1982-83 as against a marginal rise of 0.7 per cent in 1982-83 over 1981-82. The average index number of Industrial production in the State (adjusted for seasonality) recorded an increase of 4.7 per cent during the first five months of 1985 compared to the corresponding period of previous year.
Andhra Pradesh